THE MAINTENANCE OF LIFEBOAT: A CASE STUDY OF MV. MAJU 99 - I Komang Hedi Pramana Adiputra; Ryan Puby Sumarta; Anjas Irmansyah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pelayaran Malahayati, 2023)
Lifeboats are one of the safety equipment used to leave the ship in the emergency situation which aims to save the lives of the crew on the ship. Lifeboats must always be in a ready-to-use condition, so maintenance is required in accordance with applicable regulations. The purpose of this study was to determine the obstacles and method when carrying out lifeboat maintenance in KM. Maju 99. The type of research is a qualitative research through observation, documentation and literature study to collect data. The result of this study is the maintenance of lifeboats in KM. Maju 99 is in accordance with SOLAS 1974 and PMS (Plan Maintenance System) from the company, but the lack of time and spare parts in carrying out maintenance is the obstacles in the implementation of lifeboats maintenance. Data analysis resulted in the conclusion that several factors such as knowledge of the crew, time management and availability of spare parts must be considered in carrying out lifeboats maintenance.